Impact of the pediatric 13-valent pneumococcal conjugate vaccine on serotype distribution and clinical characteristics of pneumococcal pneumonia in adults: The Japan Pneumococcal Vaccine Effectiveness Study (J-PAVE). Issue 20 (6th May 2019) - Sando, Eiichiro; Suzuki, Motoi; Furumoto, Akitsugu; Asoh, Norichika; Yaegashi, Makito; Aoshima, Masahiro; Ishida, Masayuki; Hamaguchi, Sugihiro; Otsuka, Yoshihito; Morimoto, Konosuke
Highlights: The PCV13 serotypes were associated with severe clinical manifestations. Introducing pediatric PCV13 decreased vaccine-type-pneumococcal pneumonia in adults. Serotype distribution has changed in adult pneumococcal pneumonia in Japan. Abstract: Background: The pediatric 13-valent pneumococcal conjugate vaccine (PCV13) was included in the pediatric immunization programme in Japan in late 2013. The impact of vaccination on the serotype distribution and clinical characteristics of pneumococcal pneumonia has not been described. Methods: The first phase of this multicentre prospective study was conducted at community-based hospitals in Japan from 2011 to 2014. The second phase was conducted from 2016 to 2017. Pneumococcal isolates and clinical data were collected from patients with community-acquired pneumonia who were ≥15 years of age. Patients were classified by pneumococcal serotype to PCV13 serotype, 23-valent pneumococcal polysaccharide vaccine (PPV23) non-PCV13 serotype, and non-vaccine serotype. Results: A total of 484 patients were enrolled, 241 in the first phase and 243 in the second. The proportion of PCV13 serotypes decreased from 53% to 33% ( p < 0.001), whereas PPV23 non-PCV13 serotypes did not change ( p = 0.754). PCV13 serotypes were associated with increased risk of elevated blood urea nitrogen (adjusted odds ratio 2.49; 95% confidence interval: 1.49–4.16) and hospitalization (adjusted odds ratio 1.74; 95% confidence interval: 1.02–2.95). These associations were not observed in patients with PPV23 non-PCV13 serotypes. Conclusions: The occurrence of pneumococcal pneumonia caused by vaccine-covered serotypes dramatically decreased following the introduction of pediatric PCV13. The PCV13 serotypes were associated with pneumonia severity.